ANALISA PENGENDALIAN CACAT PADA PRODUK BORDIR KOPYAH SETENGAH JADI MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL - Rohmat, Rohmat; Hidayat, Hidayat (Universitas Putera Batam, 2024)
Quality is an important aspect in the sector of a business. There is severe competition between business actors in achieving customer satisfaction through the principle of prioritizing quality over quantity. A similar thing was also done by one of the business actors in the Gesik area, namely UD Sketsa Embroidery, which is engaged in making semi-finished embroidered skullcaps. In its production, this business never knows in detail the defect causes that occur in its products and how to control them. So in this research, researchers conducted research analyzing defect control and how to improve its quality using statistical quality control methods. Based on the research results, this method can classify the types of defects that often occur, namely wrong direction embroidery defects, stacked embroidery, and unequal embroidery spacing. Knowledge of the weekly defect percentage at the time of sampling in this study was 1.57%. From the Pareto diagram, stacked embroidery type defects are the defects that have the highest number of frequencies, so stacked embroidery type defects are explained further using a fishbone diagram. This analysis is reviewed from aspects of human, machines, methods, materials and the environment factors. To prevent these defects, proposed actions and process improvements are also mentioned in this research.